Population genomics of pneumococcal carriage in Massachusetts children following introduction of PCV-13. Issue 2 (19th February 2019) - Mitchell, Patrick K.; Azarian, Taj; Croucher, Nicholas J.; Callendrello, Alanna; Thompson, Claudette M.; Pelton, Stephen I.; Lipsitch, Marc; Hanage, William P.
Abstract : The 13-valent pneumococcal conjugate vaccine (PCV-13) was introduced in the United States in 2010. Using a large paediatric carriage sample collected from shortly after the introduction of PCV-7 to several years after the introduction of PCV-13, we investigate alterations in the composition of the pneumococcal population following the introduction of PCV-13, evaluating the extent to which the post-vaccination non-vaccine type (NVT) population mirrors that from prior to vaccine introduction and the effect of PCV-13 on vaccine type lineages. Draft genome assemblies from 736 newly sequenced and 616 previously published pneumococcal carriage isolates from children in Massachusetts between 2001 and 2014 were analysed. Isolates were classified into one of 22 sequence clusters (SCs) on the basis of their core genome sequence. We calculated the SC diversity for each sampling period as the probability that any two randomly drawn isolates from that period belong to different SCs. The sampling period immediately after the introduction of PCV-13 (2011) was found to have higher diversity than preceding (2007) or subsequent (2014) sampling periods {Simpson's D 2007: 0.915 [95 % confidence interval (CI) 0.901, 0.929]; 2011:  0.935 [0.927, 0.942]; 2014 :  0.912 [0.901, 0.923]}. Amongst NVT isolates, we found the distribution of SCs in 2011 to be significantly different from that in 2007 or 2014 (Fisher's exact test P =0.018, 0.0078), but did not find a difference comparing 2007 to 2014 (Fisher's exact test P =0.24), indicating greater similarity between samples separated by a longer time period than between samples from closer time periods. We also found changes in the accessory gene content of the NVT population between 2007 and 2011 to have been reduced by 2014. Amongst the new serotypes targeted by PCV-13, four were present in our sample. The proportion of our sample composed of PCV-13-only vaccine serotypes 19A, 6C and 7F decreased between 2007 and 2014, but no such reduction was seen for serotype 3. We did, however, observe differences in the genetic composition of the pre- and post-PCV-13 serotype 3 population. Our isolates were collected during discrete sampling periods from a small geographical area, which may limit the generalizability of our findings. Pneumococcal diversity increased immediately following the introduction of PCV-13, but subsequently returned to pre-vaccination levels. This is reflected in the distribution of NVT lineages, and, to a lesser extent, their accessory gene frequencies. As such, there may be a period during which the population is particularly disrupted by vaccination before returning to a more stable distribution. The persistence and shifting genetic composition of serotype 3 is a concern and warrants further investigation.